Optimalisasi Skill Digital Melalui Implementasi Pembelajaran Program Studi Independen Di PT Revolusi Cita Edukasi (RevoU) - Miftachul Jannah; Sonja Andarini (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
In the current digital era, technological progress is increasing rapidly, where all forms of human activity can be assisted by using technology. Evidence of today's technological advances is that many industries are starting to switch to the digital sector. This is what requires students to compete in improving their digital skills considering that currently there are many jobs in the industry. To accommodate students so they can prepare the skills they need, the Ministry of Education and Culture has issued the Independent Independent Study Program for Independent Campus Learning. One of the partners in this Independent Study program is PT Revolusi Cita Edukasi (RevoU). At RevoU, students will be provided with digital skills such as Product Management, Digital Marketing, Data Analytics, and Software Engineering which are much needed in today's digital era. The learning method used by RevoU is a combination learning method such as classroom learning delivered directly by industry practitioners and learning through practice both individually and in groups to ensure students understand well the concepts and practical applications of the knowledge provided. In addition, students will also learn through case studies and simulations that provide real work experience in each field of the skills being taught. The learning outcomes of the Independent Study program at RevoU are that it can provide benefits to students so they can understand and train skills to prepare for careers in the digital industry.